2014
DOI: 10.1111/jfs.12093
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Serotype Identification by Multiplex Polymerase Chain Reaction and Antimicrobial Resistance Patterns of Listeria Monocytogenes Isolated from Retail Foods

Abstract: In the present study, a total of 512 food samples composed of raw milk, dairy products, meat/meat products, chicken meat, seafood and raw vegetables were analyzed for the presence of Listeria monocytogenes. The results of the standard identification methods showed that 20 (3.9%) of the analyzed samples were found to harbor this pathogen. Further, 8.4% (13/155) of chicken meats, 0.9% (1/105) of meat/meat products and 13.6% (6/44) of fresh vegetables were contaminated with L. monocytogenes. Interestingly, only 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 36 publications
6
20
1
Order By: Relevance
“…It was found that serotype 1/2b (or 3b) was rare with only one positive in raw milk and two positives being picked up in pasteurized milk. This is in line with most studies that have found serotypes 1/2a and 1/2b was to be the most common serotypes in food (Aarnisalo et al, 2003: Wallace et al, 2003: Cetinkaya et al 2014.…”
Section: Discussionsupporting
confidence: 79%
“…It was found that serotype 1/2b (or 3b) was rare with only one positive in raw milk and two positives being picked up in pasteurized milk. This is in line with most studies that have found serotypes 1/2a and 1/2b was to be the most common serotypes in food (Aarnisalo et al, 2003: Wallace et al, 2003: Cetinkaya et al 2014.…”
Section: Discussionsupporting
confidence: 79%
“…Cetinkaya et al . () further reported that 65% of the isolates were resistant to more than five antibiotics. However, lower multidrug resistance percentages were reported by other researchers (Rodas‐Suárez et al .…”
Section: Resultsmentioning
confidence: 96%
“…; Cetinkaya et al . ). But, the levels of resistance seem to vary by geographical locations and antimicrobial usage in humans and animals.…”
Section: Introductionmentioning
confidence: 97%
“…After assessing all the information from the recovered publications, seventy-eight primary studies [6,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,…”
Section: Methodsmentioning
confidence: 99%